Calumet Creek DOC, discharge and SWE data (SWE) - Meingast, Karl M; Kane, Evan S (PANGAEA, 2019)
Increasing concentrations of dissolved organic carbon (DOC) have been identified in many freshwater systems over the last three decades. While studies have generally nominated changes in temperature and atmospheric deposition as determinants of DOC concentrations, there is still much uncertainty concerning net effects on DOC concentrations and export dynamics. We leveraged long-term datasets (1988-2013) from a first-order tributary of Lake Superior to understand changes in DOC concentrations and exports from the watershed, particularly through snowmelt dynamics. We observed an increase in DOC concentrations of approximately 0.12 mg C L -1 year -1 , which were coincident with regional warming and declines in sulfate deposition. DOC fluxes were most strongly related to snowmelt dynamics, with peak snow water equivalencies generally being lower and less variable in the 21 st century, compared with measurements taken in the 1980s and 1990s. As a result of the countervailing changes in DOC concentrations and runoff patterns, we observed no significant trends in DOC export through time. Based on these trends, any future changes in climate that lessen the dominance of the spring freshet on annual runoff dynamics would decrease DOC export in snowmelt dominated systems, but identifying the mechanism of increasing DOC concentrations is needed to fully understand the future effects on DOC export. Together these findings illustrate complex interactions between climate and atmospheric deposition in carbon cycle processes, and highlight the importance of long-term monitoring efforts for understanding the consequences of a changing climate.
Keywords: Discharge; DOC; SWE